IMAN DAN PERBUATAN BAIK DALAM PERSPEKTIF KESELAMATAN KRISTEN - Milka Gracea; Marsali Marsali; Pransiska Dwi; Sarmauli Sarmauli (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This article examines the relationship between faith and good works from a Christian perspective. The purpose of this article is to explain that salvation is a gift from God received through faith in Jesus Christ, not the result of human effort. However, true faith always produces good works as evidence of a transformed life. The research method used is qualitative theological, with a literary study approach to the Bible and the views of theologians such as Louis Berkhof and Martin Luther. The results of the study indicate that faith and works are inseparable; faith saves, while good works are a manifestation of obedience and love for God. Good works are not a requirement for salvation, but rather a living and active expression of faith. Therefore, the balance between faith and works needs to be continuously emphasized in the education and lives of Christians so that the faith that is professed does not remain theoretical but is manifested in acts of love that glorify God.